The Influence of Live Streaming Commerce on Purchase Intention Based on the Stimulus-Organism-Response (SOR) Framework of Aerostreet Live Stream Consumers in Shopee E-Commerce - Widiastuti, Laras Prismafika; Ningrum, Nonik Kusuma; Maharani, Bernadetta Diansepti (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to explore how live streaming commerce influences purchase intention based on the stimulus-organism-response (SOR) framework for Aerostreet live stream consumers on Shopee e-commerce. This research develops a research model based on SOR theory to examine how the characteristics of live streaming commerce impact consumer behavioral responses, namely purchase intention. Sampling used a purposive sampling technique through a questionnaire with a sample of 200 respondents. Respondents who met these requirements were then analyzed using the SPSS version 20 program. The results of this study showed that interactivity had a positive and significant effect on trust, visualization had a positive and significant effect on trust, entertainment had a positive and significant effect on trust, professionalization had a positive and significant effect on trust, trust has a positive and significant effect on purchase intention and live streaming commerce has a positive effect on purchase intention.